Shifting Religious Practices: The Impact of Digitalization on Islamic Rituals in Indonesian Pesantren - Imam Yahya; Muhammad Aflahmuna Ananda; Rokhmadi; Ferry Khusnul Mubarok (UIN Raden Mas Said Surakarta, 2024)
This study aims to analyze the effectiveness of religious digitalization within Indonesian Muslim communities. Practices such as online communal prayers, online tahlil, online istighosah, and online religious lectures have become new forms of religious traditions in the post-COVID-19 pandemic era. However, some Muslim communities reject these digitalized forms of religiosity for fundamental reasons. The findings reveal that the rejection of religious digitalization is influenced by three main factors. First, concerns over the loss of authenticity in religious texts within the digital realm. Second, apprehensions regarding the shift of religious authority from classical scholars to digital-based preachers or ulama. Third, fears of religious desacralization, where the sacred values of religion are perceived to be replaced by the realities of digital media. This study provides essential insights into the challenges of integrating digital technology with traditional religious practices and fosters further discussion on the implications of digital transformation for religiosity in the modern era.